Sound Theory at Grand Theory’s End (Sound Stage Screen, 2022)
Review of Sound Objects. Edited by James A. Steintrager and Rey Chow. Durham, NC: Duke University Press, 2019. 312 pp. ISBN 9781478001454 (paperback).